2008
DOI: 10.1037/0022-006x.76.4.633
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal investigation of interpersonal violence in relation to mental health and substance use.

Abstract: The authors examined longitudinally the mental health status of women as a function of different types and combinations of exposure to interpersonal violence. A structured telephone interview was administered to a household probability sample of 4,008 women (18-89 years of age), who were then recontacted for 1- and 2-year follow-up interviews. Interviews assessed lifetime violence history (i.e., sexual assault, physical assault, witnessed serious injury or violent death), past-year mental health functioning (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
167
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(184 citation statements)
references
References 93 publications
14
167
2
Order By: Relevance
“…For instance, the speed at which women with and without a SAH respond (i.e., how long they stay in the scene) is a primary difference reported in the literature. However, no studies to-date have controlled for depressive symptoms, which are common in sexual assault survivors [22,23] and are related to psychomotor slowing [24] and slower processing speed [25]. Similarly, a recent study utilized a written vignette and replicated the finding that women with a SAH left later in the scene [26].…”
Section: Introductionmentioning
confidence: 69%
“…For instance, the speed at which women with and without a SAH respond (i.e., how long they stay in the scene) is a primary difference reported in the literature. However, no studies to-date have controlled for depressive symptoms, which are common in sexual assault survivors [22,23] and are related to psychomotor slowing [24] and slower processing speed [25]. Similarly, a recent study utilized a written vignette and replicated the finding that women with a SAH left later in the scene [26].…”
Section: Introductionmentioning
confidence: 69%
“…In addition, the well-known relationship between even a single traumatic event and the development of PTSD or other psychiatric problems 39 is strengthened following multiple occurrences of trauma, particularly physical assaults. 8,40 For drug users who are not in treatment, the occurrence of new traumatic events is likely to destabilize progress toward healthy behavior change by intensifying psychiatric and drug use severity, 8,17,41 which, in turn, increases risk of further traumatic event exposure. Future studies should assess the mental health outcomes related to these very high re-exposure rates, with particular attention to the greater risk for women injecting drug users.…”
Section: Implications Of Traumatic Event Re-exposurementioning
confidence: 99%
“…6,7 The clinical relevance of these data is clear from studies that show that traumatic event reexposure alone or followed by PTSD increases the risk of further psychiatric impairment, including both PTSD and drug use. [6][7][8] There is good reason to believe that urban drug users experience a considerable amount of traumatic event re-exposure. Drug use, urban living, and low income are each associated with elevated risk of traumatic event exposure and re-exposure.…”
Section: Introductionmentioning
confidence: 99%
“…For victims developing PTSD after a trauma the risk of developing PTSD also after a subsequent trauma is heightened (Briere and Jordan, 2004;Breslau, Peterson and Schultz, 2008). Some researchers have also suggested that prior merely stressful life events may have a sensitizing effect, making victims of a trauma more prone to develop PTSD (Lloyd and Turner, 2003;Hedtke, Ruggiero, Fitzgerald et al, 2008). Experiencing high level of community violence has been associated with increased severity of symptoms of PTSD above and beyond the trauma that was used as the reference for reporting PTSD symptoms.…”
Section: Interpersonal Violence and Symptoms Of Psychological Ill-healthmentioning
confidence: 99%